E-Busse in Deutschland: Status und Perspektive. Erste Erfahrungen aus der Begleitforschung Bus des BMVI. - Faltenbacher, Michael (DVV Media Group, 2019)
Es werden die Inhalte und Ziele der Begleitforschung Bus des BMVI zur ganzheitlichen Bewertung der Praxistauglichkeit und Einsatzreife der implementierten E-Bussysteme sowie die gemeinsam von BMU und BMVI initiierte Arbeitsgruppe Bus als Plattform für den Erfahrungsaustausch vorgestellt. Erste Auswertungen zu Betriebserfahrungen im Rahmen der aktuell vom Bund geförderten Projekte werden präsentiert. Ein weiterer Schub für den E-Busmarkt ist über die Clean Vehicle Directive mit ihren verbindlichen Neubeschaffungsquoten für saubere und emissionsfreie Busse zu erwarten.

The contents and objectives of the accompanying research on electric busses for the German Federal Transport Ministry (BMVI) are presented. It focuses on the holistic evaluation of the technological and operational readiness of the deployed E-bus systems. First initial evaluations of operating experiences from projects currently funded by the Federal Government are presented. The accompanying research on E-buses is part of the working group "Innovative drivetrain for buses", which was initiated jointly by the federal ministries for the environment (BMU) and transport as a platform for the exchange of hands on experiences from daily operation between the different stakeholders. Another boost for the e-bus market is to be expected via the European Clean Vehicle Directive with its binding new purchase quotas for clean as well as zero-emission buses.
Electric buses in Germany: status and perspectives.
Keywords: Verkehr; Stadtverkehr; Regionalverkehr; ÖPNV; Busverkehr; Verkehrsunternehmen; Verkehrsbedienung; Elektrofahrzeug; Elektromobilität; Stromversorgung; Ladeinfrastruktur; Energiebedarf; Verfügbarkeit; Bewertung; Zukunftsperspektive